FORMULASI STRATEGI DALAM MENINGKATKAN LOAD FACTOR PENERBANGAN CENGKARENG-SOLO - Basri Fahriza; Badzlina Anindya; Peppy Fachrial (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
The purpose of the research is to analyze the internal and external factors faced by NAM AIR and formulates the strategy to increase the Load Factor. The method was qualitative with observation technique, interview, library research, and SWOT analysis. The result shows that IE matrics for external factors evaluation is 3.04 and the internal is 2.91. It means that NAM AIR is in quadrant II. While NAM AIR is in quadrant I based on the Grand Strategy matrics of strength and weakness factors (1.23) and opportunity and threat factors (0.86). Both results conclude that the best formulated strategy is market penetration.